Hand deformities in a young male patient. - Algarra-Sahuquillo, J.; Arteaga-Henríquez, M.; Rodríguez-Rodríguez, R.-N.; Fagundo-González, E. (European Journal of Pediatric Dermatology, 2021)
Pachydermodactyly is a rare digital fibromatosis which presents with asymptomatic soft tissue swelling of the proximal interphalangeal joints. Its etiology remains unknown and only few cases have been reported in the literature. We report a new case of a 22-year-old male with typical lesions to raise awareness of the importance of an adequate diagnosis and to avoid unnecessary procedures as it can mimic inflammatory joint diseases.